High number of granzyme B expressing CTLs predicts worst prognosis of nasopharygeal carcinoma patients - Harijadi, Harijadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Nasopharyngeal carcinoma (NPC) characteristically harbors many tumor-infiltrating lymphocytes. In biopsies of Hodgkin or anaplastic large cell lymphoma many activated CTLs are related to a very poor clinical outcome, suggesting that in these cases with a strong CTL mediated anti-tumor cell response, selection occurs for tumor cells that have become resistant to CTL and chemo and/or radiotherapy induced apoptosis. Only activated CTLs and natural killer cells express granzyme B.Objective. Since, similar to lymphomas, the prognosis of NPC patients depends primarily on the sensitivity of tumor cells to radio- and/or chemotherapy, this study investigated whether the presence of many tumor-infiltrating activated CTLs in tumor biopsies also predicts poor prognosis in NPC patients.Methods: The study investigated 39 specimens of Indonesian NPC patients that fulfilled the following criteria; no evidence of distant metastases at the time of diagnosis, and complete remission following complete radio- and/or chemotherapy. Number of tumor-infiltrating activated CTLs was detected using a combination of antibodies against granzyme Band CD3, CD8 and CD56.Results: The presence of a high number of tumor infiltrating activated CTLs expressing granzyme B appeared to be a very strong predictor of a rapid fatal clinical outcome. Its prognostic value was stronger than and independent from the other prognostic makers; age and clinical TNM stage at presentation. Prognosis was found to decline strongly with increasing percentage of activated CTLs. The most informative cut-off value was found to be 25%. The median overall survival time of patients with